META-ANALISIS : PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS PESERTA DIDIK - Lenti Supriwardi; Zulyusri Zulyusri; Lufri Lufri (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study was to analyze the effect of the Problem based learning model on students' scientific literacy skills. This research method is a meta-analysis by examining data sources originating from national or international journals published in the last five years (2017-2021). The results showed that the meta-analysis study had an effect on students' scientific literacy skills with the Problem Based Learning Model. The results of the analysis showed that the 14 effect sizes of the analyzed studies were heterogeneous (Q = 64,264, p < 0,001). The results of the analysis using the random effects model showed that the problem based learning model had a positive and significant effect on the scientific literacy ability of students ( z = 6,374, p < 0,001). The problem based learning model has an effect on the scientific literacy ability of students, including in the very large category of 1,021.